2022
DOI: 10.1007/s40273-022-01212-z
|View full text |Cite
|
Sign up to set email alerts
|

The Costs of Dementia in Europe: An Updated Review and Meta-analysis

Abstract: Background and ObjectiveThe prevalence of dementia is increasing, while new opportunities for diagnosing, treating and possibly preventing Alzheimer's disease and other dementia disorders are placing focus on the need for accurate estimates of costs in dementia. Considerable methodological heterogeneity creates challenges for synthesising the existing literature. This study aimed to estimate the costs for persons with dementia in Europe, disaggregated into cost components and informative patient subgroups. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 134 publications
0
15
0
Order By: Relevance
“…Wimo and colleagues found that informal care makes up 44% of total costs in high‐income countries and rises to 85% of the total cost for low‐income countries 25 . Even within Europe there is significant variation in the level of reliance on informal care, with informal care making up ≈75% of total cost in southern Europe and only 25% of total cost in the Nordic region 26 . These differences are likely due to a mix of cultural factors and variation in the amount and types of support policies in place for caregivers 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wimo and colleagues found that informal care makes up 44% of total costs in high‐income countries and rises to 85% of the total cost for low‐income countries 25 . Even within Europe there is significant variation in the level of reliance on informal care, with informal care making up ≈75% of total cost in southern Europe and only 25% of total cost in the Nordic region 26 . These differences are likely due to a mix of cultural factors and variation in the amount and types of support policies in place for caregivers 27 …”
Section: Discussionmentioning
confidence: 99%
“…25 Even within Europe there is significant variation in the level of reliance on informal care, with informal care making up ≈75% of total cost in southern Europe and only 25% of total cost in the Nordic region. 26 These differences are likely due to a mix of cultural factors and variation in the amount and types of support policies in place for caregivers. 27 Our forecasts illustrate the impact of rising dementia prevalence, with total costs increasing by over 50% between 2019 and 2050, even if costs per prevalent case stay constant.…”
Section: Total Costsmentioning
confidence: 99%
“…While Memento and ADC obtained information from clinical follow‐up with patients and caregivers. We decided to create separate states for institutionalization given that the costs and mortality rates differ widely compared to those living in the community 17,18 …”
Section: Methodsmentioning
confidence: 99%
“…We decided to create separate states for institutionalization given that the costs and mortality rates differ widely compared to those living in the community. 17 , 18 …”
Section: Methodsmentioning
confidence: 99%
“…The care structure for persons with dementia and the resource utilization and costs of dementia care differs substantially across Europe, both between and within countries and between majority and ethnic minority populations. 28 Simplifying, Northern European countries tend to have higher availability of formal care services such as home help and nursing homes, while in Southern Europe family caregivers provide most of the care. 29 Thus, the opportunity for offsetting high drug costs with lower costs for formal care differ substantially across countries, and the evidence for such offsets currently comes only from model projections.…”
Section: Consequences For Inequalities In Access and Healthmentioning
confidence: 99%